Konstruksi Teori dalam Proses Pembelajaran - Lutfi, M.; A, Arifuddin; S, Saprin (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Learning theory, which is a set of principles, ideas, concepts, and procedures that can be tested and analyzed, as well as having a function in explaining the process of learning interaction between teachers and students. Learning is defined as the process of relatively permanent change in behavior due to reinforced experience or training. Learning activities involve the interaction of the individual with the environment and produce behavioral changes both cognitively, affectively, and psychomotorically. Further, factors affecting the teaching and learning process, both internal in nature such as maturity, readiness, psychological condition and health of the learners; as well as external ones such as family, school, and community environments. An understanding of these factors is important for creating learning approaches that are adaptive and responsive to student needs. Theory construction in education is described through two main approaches: deductive and inductive. Deductive construction starts from basic postulates or assumptions to generate hypotheses that are then tested through experiments. In contrast, the inductive approach gathers empirical facts to form generalizations and compiles theories gradually from the bottom up. The generated theory needs to be verified to test its validity, using syntactic (internal logic of the theory), semantic (predictive ability and validity), and parsimony (simplicity of the theory compared to other equally strong theories logically and empirically) approaches. Psychology helps teachers identify students needs, abilities, and behaviors, as well as choose effective learning strategies. Teachers are also demanded to have pedagogical and professional competencies, including in terms of techniques of studying student behavior, analyzing learning processes, as well as adapting teaching methods according to diverse learning styles.